Quantity and quality losses of 'Crimson Seedless' grape and 'Packham's Triumph' pear along the supply chain and associated impacts - Blanckenberg, Anelle (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.